2018
DOI: 10.1002/ceat.201700575
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production from Rubber Seed Oil by Transesterification Using a Co‐solvent of Fatty Acid Methyl Esters

Abstract: Rubber seed oil (RSO) is a high‐potential feedstock for the production of biodiesel fuel (BDF) in Asia. Transesterification using fatty acid methyl esters (FAMEs) as co‐solvents was developed for BDF production from RSO with high content of free fatty acids (FFAs). The homogeneous system (FAMEs/triglyceride/methanol) was attained when the FAME content was more than 30 wt %. After esterification of RSO, the crude RSO obtained was transesterified with FAMEs as a co‐solvent. The quality of BDF with high FAME cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 32 publications
0
20
0
2
Order By: Relevance
“…Typical biodiesel production employs an esterification or/and transesterification process, where esterification is a process of reaction between alcohol and carboxylic acid such as free fatty acid using an acid catalyst, while transesterification involves a reaction between triglyceride and alcohol, yielding fatty acid methyl ester and alcohol (Kirumakki et al 2006). Figure 1 shows the transesterified biodiesel fuel (BDF) from rubber seeds (Le et al 2018). Wibowo (2013) produced an environmentally friendly high yield biodiesel with controllable density and viscosity by an in-situ transesterification that entails the extraction of oil from rubber seed kernel and a reaction with methanol using a sulfuric acid catalyst.…”
Section: Main Usagementioning
confidence: 99%
See 2 more Smart Citations
“…Typical biodiesel production employs an esterification or/and transesterification process, where esterification is a process of reaction between alcohol and carboxylic acid such as free fatty acid using an acid catalyst, while transesterification involves a reaction between triglyceride and alcohol, yielding fatty acid methyl ester and alcohol (Kirumakki et al 2006). Figure 1 shows the transesterified biodiesel fuel (BDF) from rubber seeds (Le et al 2018). Wibowo (2013) produced an environmentally friendly high yield biodiesel with controllable density and viscosity by an in-situ transesterification that entails the extraction of oil from rubber seed kernel and a reaction with methanol using a sulfuric acid catalyst.…”
Section: Main Usagementioning
confidence: 99%
“…Wibowo (2013) produced an environmentally friendly high yield biodiesel with controllable density and viscosity by an in-situ transesterification that entails the extraction of oil from rubber seed kernel and a reaction with methanol using a sulfuric acid catalyst. Le et al (2018) used a similar method in which the rubber seed oil was (RSO) was esterified and transesterified using fatty acid methyl esters (FAME) as a co-solvent. They revealed that the quality of the derived biodiesel fuel (BDF) with high FAME content met the criteria of the EN14214 ( 2008) and JIS K2390 ( 2016) standards (Le et al 2018).…”
Section: Main Usagementioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][15][16][17] The objective of this study is to report the preparation of sustainable sulfur-containing polymer by inverse vulcanization of sulfur with rubber seed oil, RSO (a non-edible vegetable oil) for the very first time. The selection of RSO, which originates from the rubber plant (Hevea Brasiliensis) heavily grown in Southeast Asian countries such as Malaysia and Indonesia, [42] was motivated by its source abundance (rubber seeds) that disposed off as low-cost biomass with limited usage. [43] The analytical studies show that it contains almost 18.9 % saturated fatty acids and 80.5 % unsaturated fatty acids (oleic acid 24.6 %, linoleic acid 37.28 %, and linolenic acid 19.22 %).…”
Section: Introductionmentioning
confidence: 99%
“…[43] The analytical studies show that it contains almost 18.9 % saturated fatty acids and 80.5 % unsaturated fatty acids (oleic acid 24.6 %, linoleic acid 37.28 %, and linolenic acid 19.22 %). [42][43][44][45][46] The initial sulfur content of the copolymers was varied to investigate its effect on the copolymers' properties and the obtained new polymers were characterized with different techniques including FTIR, SEM-EDX-mapping, p-XRD, TGA, and DSC. Also, for the first time, the effect of the post-polymerization treatment (curing and quenching) on inverse vulcanized copolymers have been investigated.…”
Section: Introductionmentioning
confidence: 99%